Inside Cover: High‐Performance Visible‐Light‐Driven Pt/CdS/Graphene Photoelectrocatalysts for Methanol Oxidation (Energy Technol. 8/2017). Issue 8 (23rd May 2017) - Zhai, Chunyang; Hu, Jiayue; Sun, Mingjuan; Zhu, Mingshan
Abstract : Visible‐light‐driven methanol oxidation : Fuel cells, as a technology for the conversion of chemical energy into electrical energy, have been recognized as a promising sustainable power source. Traditional electrocatalysts together with optically active semiconductors are selected as promising catalysts for the improvement of anodic reactions. The cover image depicts cadmium sulfide (CdS)‐decorated reduced graphene oxide (RGO) as photo‐activated support for depositing Pt nanoparticles. The ternary Pt/CdS/RGO catalysts displayed enhanced activity and stability of methanol oxidation under visible light irradiation. The synergistic effect of the RGO nanosheets and photo‐irradiation promote the electrocatalytic performance and stability. This work provides a new insight into developing highly efficient photo‐electrocatalysts for application in direct methanol fuel cells in the presence of visible‐light illumination. More details can be found in the Full Paper by Prof. Zhu's group from Ningbo University onpage 1192 in Issue 8, 2017 (DOI:10.1002/ente.201600637 ).